Kluyvera ascorbata: An Emerging Pathogen and Rare Cause of Urinary Tract Infection in Immunocompetent Patients at a Tertiary Care Center in North India - Apurva Rautela; Nikhil Raj; Vikramjeet Singh; Anupam Das; Jyotsna Agarwal (Archives of Medicine and Health Sciences)
Kluyvera spp. is a Gram-negative bacillus and was discovered by Kluyver and van Niel, included in the family Enterobacteriaceae. We report two cases of urinary tract infection due to Kluyvera ascorbata. The first case was a 61-year-old male, who was admitted to the nephrology department of the hospital with chief complaints of fever with chills from 1 week, abdominal pain, and difficulty in passing urine. The second case was a 29-year-old female, who presented to the medicine department of the hospital with a 4-day history of fever with associated chills and rigor, abdominal pain, chills, and weakness. These patients were treated with nitrofurantoin given orally for 7 days they recovered completely. This case series highlights the role of K. ascorbata, and in general of Kluyvera species, as an unusual but potentially dangerous pathogen, the need for prompt identification to determine potential pathogenicity in the immunocompetent as well as in the immunocompromised host, and to assess the efficacy of antibiotics such as carbapenems and nitrofurantoin.